THE INFLUENCE OF TEMPERATURE ON THE ALUMINUM ALLOYS - Andrei DIMITRESCU; Florin BACIU (Fiabilitate şi Durabilitate, 2013)
In the technical literature are some correlations with reference to the influence of brazing temperatureon aluminum alloys, but there is not a diagram generally accepted.This paper aims to establish a direct correlation between the mechanical properties and the retentiontime of the brazing temperature. The experiments were applied on samples of aluminum alloy 3L59. Theretention time varies from T1 = 10 minutes to T3 = 30 minutes